A matched-group study protocol to evaluate the implementation of an Integrated Care Pathway programme for chronic obstructive pulmonary disease in Singapore. Issue 1 (7th January 2015) - Wu, Christine Xia; Tan, Woan Shin; See, Ryan Chor Kian; Yu, Weichang; Kwek, Lynette Siang Lim; Toh, Matthias Paul Han Sim; Chee, Thong Gan; Chua, Gerald Seng Wee
Abstract : Introduction: The treatment of chronic obstructive pulmonary disease (COPD) involves different care providers across care sites. This fragmentation of care increases the morbidity and mortality burden, as well as acute health services use. The COPD-Integrated Care Pathway (ICP) was designed and implemented to integrate the care across different sites from primary care to acute hospital and home. It aims to reduce the prevalence of COPD among the population in the catchment, reduce risk of hospital admissions, delay or prevent the progression of the disease and reduce mortality rate by adopting a coordinated and multidisciplinary approach to the management of the patients' medical conditions. This study on the COPD-ICP programme is undertaken to determine the impact on processes of care, clinical outcomes and acute care utilisation. Methods and analysis: This will be a retrospective, pre-post, matched-groups study to evaluate the effectiveness of the COPD-ICP programme in improving clinical outcomes and reducing healthcare costs. Programme enrolees (intervention group) and non-enrolees (comparator group) will be matched using propensity scores. Administratively, we set 30% as our target for proportion admission difference between programme and non-programme patients. A sample size of 62 patients in each group will be needed for statistical comparisons to be made at 90% power. Adherence with recommended care elements will be measured at baseline and quarterly during 1-year follow-up. Risk of COPD-related hospitalisations as primary outcome, healthcare costs, disease progression and 1-year mortality during 1-year follow-up will be compared between the groups using generalised linear regression models. Ethics and dissemination: This protocol describes the implementation and proposed evaluation of the COPD-ICP programme. The described study has received ethical approval from the NHG Domain Specific Review Board (DSRB Ref: 2013/01200). Results of the study will be reported through peer-review publications and presentations at healthcare conferences.